Case report: The effect of induction targeted therapies in stage III driver mutants non-small cell lung cancer - Kian, Waleed; Krayim, Belal; Giles, Betsy; Elkiaan, Nasim A.; Idris, Amjad; Fink, Daniel; Peled, Nir; Roisman, Laila C. (Frontiers in Oncology, 2024)
Background: Over the past decade, progress in the diagnosis and treatment of Non-Small Cell Lung Cancer (NSCLC) has led to the identification of many targeted mutations. This has enhanced PFS and OS in both advanced and early-stage NSCLC. The current standard of care for stage III NSCLC varies, and it may combine chemotherapy with either immunotherapy or radiotherapy. This study evaluated the role of induction-targeted therapies in patients with driver mutations and inoperable NSCLC. Methods: This is a single-center, retrospective study assessing the efficacy of targeted therapy in resectable stage III NSCLC patients who are EGFR or ALK-positive, using patient records, PET-CT, brain MRI staging, and mediastinal lymph node evaluation. Results: Between January 2020 and February 2024, we identified four patients with either EML4-ALK fusions (2/4) or EGFR mutations (2/4) who underwent treatment with brigatinib or osimertinib before surgery. All patients experienced clinical benefits. Of the two patients with ALK fusion, one responded almost completely, while the other exhibited a notable partial response. Among the patients with EGFR mutations, one had a complete response and the other displayed a significant partial response. All four patients subsequently underwent lobectomy surgical resection. Conclusions: This case series highlights the potential of targeted therapies for resectable NSCLC in the neoadjuvant setting. Further research is required to confirm their benefits, assess their safety and efficacy, and determine optimal timing and sequencing.